THE DOMINATION OF PATRIARCHISM IN INHERITANCE CUSTOMARY SYSTEMS - Adhi Dwipayana; Nyoman Astawan (Universitas Negeri Makassar, 2021)
There are two objectives to be achieved by this study, first revealing the dominance of patriarchism in systems of inheritance. Secondly, revealing efforts to represent resistance to the customary systems of inheritance in literary works of Balinese cultural background. Theoretically, this research has an urgency for the development of literary discourse, while practically giving an understanding to the public about the attitude of inheritance issues in Bali. Theories of literary sociology and feminism are used as a basic foundation for analyzing the problems offered in this study. The main data sources of the research are two novels by Oka Rusmini, namely Tarian Bumi and Kenanga and two short stories by Putu Fajar Arcana, namely Sulasih and Wardani Marriage. After the data has been collected using the literature study method, then it is analyzed based on a descriptive qualitative method. The results show that the dominance of patriarchism in the adat system of inheritance has created social inequality. The customary inheritance system rules in literary works (Tarian Bumi, Kenanga, Sulasih, and Pernikahan Wardani) are monolithic, showing no partiality towards girls. Daughters who have “ninggal kedaton” (married) do not get a family “gunakaya” inheritance (gono gini). Efforts to resist patriarchal domination as represented in various literary works, starting with the character Luh Sadri, took repressive actions to sue for the distribution of inheritance, deceit, and be tough.